2019
DOI: 10.3390/fermentation5020049
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production from Cheese Whey and Expired Milk by the Brown Rot Fungus Neolentinus lepideus

Abstract: The basidiomycete brown rot fungus Neolentinus lepideus is capable of assimilating and fermenting lactose to ethanol with a conversion yield comparable to those of lactose-fermenting yeasts. The ability of the fungus to ferment lactose is not influenced by the addition of glucose or calcium. Therefore, N. lepideus may be useful in ethanol production from materials composed mainly of lactose, such as cheese whey or expired cow’s milk. Whey is a by-product of cheese manufacturing, and approximately 50% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…The process occurs regardless of the whey concentration, but it needs to be deproteinized. Therefore, N. lepideus may be useful in the ethanol production from materials consisting mainly of lactose, such as cheese whey or expired cow's milk (Okamoto et al, 2019).…”
Section: Fig 5 Generalized Process Of Ethanol Synthesis From Cheese Wheymentioning
confidence: 99%
“…The process occurs regardless of the whey concentration, but it needs to be deproteinized. Therefore, N. lepideus may be useful in the ethanol production from materials consisting mainly of lactose, such as cheese whey or expired cow's milk (Okamoto et al, 2019).…”
Section: Fig 5 Generalized Process Of Ethanol Synthesis From Cheese Wheymentioning
confidence: 99%
“…Basidiomycete fungi are forest decomposers exhibiting lignocellulosic decomposing ability, while some, such as yeast, exhibit fermentability and can produce ethanol from lignocellulosic biomass [22][23][24][25][26]. Furthermore, several studies have focused on the fermentability of wild basidiomycete fungi and revealed that ethanol can be produced from unused resources, such as rice straw, wheat bran, kitchen waste, whey, and expired milk [27][28][29][30][31][32][33]. Since these bioethanol production methods do not use recombinant microorganisms, they are environmentally friendly and can be used for regional on-site production.…”
Section: Introductionmentioning
confidence: 99%
“…The compositional analysis of the onset material usually outlines the deployment of subsequent valorization routes within a biorefinery concept to generate high added-value products along with zero waste. For instance, up to date, the vast majority of studies related to the utilization of CW through bioconversion processes implement the application of microbial entities able to consume lactose [3][4][5][6]. As a result, the range of end-applications, particularly sustainable food production, is restricted.…”
Section: Introductionmentioning
confidence: 99%